Personal correlates of problematic types of social media and mobile phone use in emerging adults - Kavčič, Tina; Levpušček, Melita; Zupančič, Maja; Poredoš, Mojca; Bjornsen, Chris (Human Technology, 2019)
We investigated the occurrence of selected types of problematic social media and mobile phone use in emerging adults, specifically social media and mobile phone overuse, phubbing, creeping, and catfishing. Contemporaneous relations with age, gender, and Big Five personality traits were examined. The participants comprised 459 Slovenian emerging adults, aged 18 to 29 years (68% female). The results suggest that problematic behaviors associated with social media and mobile phone use, with the exception of catfishing, are relatively common among young people. The examined behaviors were negatively related to age, and overuse of mobile phones, social media, and creeping were more prevalent in females than males. The Big Five personality traits, most notably high neuroticism and low conscientiousness, uniquely predicted problematic social media and mobile phone use, after accounting for age, gender, and time spent on social media. Mobile phone overuse and phubbing were also associated with high extraversion and low openness, while low agreeableness was related to creeping and catfishing.